Coexistence of Distinct Supramolecular Assemblies in Solution and in the Solid State. Issue 10 (10th January 2017) - Reddy, G. N. Manjunatha; Huqi, Aida; Iuga, Dinu; Sakurai, Satoshi; Marsh, Andrew; Davis, Jeffery T.; Masiero, Stefano; Brown, Steven P.
Abstract: Invited for the cover of this issue is the group of Steven P. Brown at the University of Warwick and collaborators in Italy and the US. The image depicts the transformation (studied by NMR spectroscopy) between small molecule building blocks into unique assemblies during solid‐solution interconversions. Read the full text of the article at10.1002/chem.201604832 . Abstract : " The idea came after stimulating discussions, as part of a collaboration between Warwick, Maryland and Bologna " Read more about the story behind the cover in the Cover Profile and about the research itself on page 2315 ff. (DOI:10.1002/chem.201604832 ).